Development and validation of a standardized double‐blind, placebo‐controlled food challenge matrix for raw hazelnuts. Issue 1 (26th January 2018) - Vandekerckhove, Marjolein; Van Droogenbroeck, Bart; De Loose, Marc; Coudijzer, Katleen; Coppens, Marc; Gevaert, Philippe; Lapeere, Hilde
Abstract: Background: Double‐blind, placebo‐controlled food challenge (DBPCFC) is considered the gold standard for food allergy diagnosis. However, this test is rarely performed routinely in clinical practice because of various practical issues, e.g. the lack of a standardized matrix preparation. The aim of this study was to develop and validate a convenient DBPCFC matrix, that can easily be implemented in daily clinical practice. The focus of this study was the blinding of hazelnuts, whereby the hazelnuts retained as much as possible their allergenicity and could be mixed homogenously in low‐doses to the matrices. Methods: A basophil‐activation test (BAT), microbial tests and an LC‐MS/MS test were performed to assess respectively the allergenicity of the used hazelnuts, the microbial stability of the novel developed matrices and the homogeneity of the hazelnuts in the matrices. A sensory test was conducted to validate the blinding of the hazelnuts in the matrices. A pilot DBPCFC study included eight patients as proof of concept. Results: The BAT‐test gave the first insights concerning the retained allergenicity of the hazelnuts. The microbial safety could be assured after 12 months of storage. Sufficient masking was assessed by several sensory tests. Homogeneous hazelnut distribution could be achieved for the different hazelnut concentrations. The DBPCFC's results showed diverse allergic responders (from no reactions to distinct objective symptoms). Conclusion: A novel stable and validated DBPCFC matrix using raw hazelnuts has been developed that allows easy preparation in a standardized way for convenient use in daily clinical practice. Trial registration EC Project number: EC/2015/0852; Date of registration: 13 Oct 2015; End date: 01 Feb 2017